Dilute doping, defects, and ferromagnetism in metal oxide systems - Ogale, Satishchandra B. (Advanced Materials, 2010)
Over the past decade intensive research efforts have been carried out by researchers around the globe on exploring the effects of dilute doping of magnetic impurities on the physical properties of functional non-magnetic metal oxides such as TiO2 and ZnO. This effort is aimed at inducing spin functionality (magnetism, spin polarization) and thereby novel magneto-transport and magneto-optic effects in such oxides. After an early excitement and in spite of some very promising results reported in the literature, this field of diluted magnetic semiconducting oxides (DMSO) has continued to be dogged by concerns regarding uniformity of dopant incorporation, the possibilities of secondary ferromagnetic phases, and contamination issues. The rather sensitive dependence of magnetism of the DMSO systems on growth methods and conditions has led to interesting questions regarding the specific role played by defects in the attendant phenomena. Indeed, it has also led to the rapid re-emergence of the field of defect ferromagnetism. Many theoretical studies have contributed to the analysis of diverse experimental observations in this field and in some cases to the predictions of new systems and scenarios. In this review an attempt is made to capture the scope and spirit of this effort highlighting the successes, concerns, and questions.